2022
DOI: 10.1186/s13052-021-01196-0
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal dexmedetomidine and intranasal ketamine association allows shorter induction time for pediatric sedation compared to intranasal dexmedetomidine and oral midazolam

Abstract: Background Non-painful diagnostic procedures require an inactive state for a prolonged time, so that sedation is often needed in younger children to perform the procedures. Our standard of care in this setting consists of the association between oral midazolam (0.5 mg/kg) and intranasal dexmedetomidine (4 mcg/kg). One of the limits of this approach is that the onset of action is quite delayed (up to 55 min) and poorly predictable. We chose to compare this association with intranasal-ketamine an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 9 publications
0
18
1
Order By: Relevance
“…We have been investigating a convenient and effective sedation regimen to manage anxiety and minimize psychological trauma in children having MRI examinations. Recent advancements in the administration of dexmedetomidine–midazolam combination therapy revealed that these two drugs combination provided an alternative for MRI sedation in children ( 11 13 , 21 ). Success rates of 82.5–84% were obtained using intranasal dexmedetomidine combined with oral midazolam ( 11 , 13 ), whereas success rate of 88–95% was observed when utilizing intranasal dexmedetomidine–midazolam combination ( 12 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have been investigating a convenient and effective sedation regimen to manage anxiety and minimize psychological trauma in children having MRI examinations. Recent advancements in the administration of dexmedetomidine–midazolam combination therapy revealed that these two drugs combination provided an alternative for MRI sedation in children ( 11 13 , 21 ). Success rates of 82.5–84% were obtained using intranasal dexmedetomidine combined with oral midazolam ( 11 , 13 ), whereas success rate of 88–95% was observed when utilizing intranasal dexmedetomidine–midazolam combination ( 12 , 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advancements in the administration of dexmedetomidine–midazolam combination therapy revealed that these two drugs combination provided an alternative for MRI sedation in children ( 11 13 , 21 ). Success rates of 82.5–84% were obtained using intranasal dexmedetomidine combined with oral midazolam ( 11 , 13 ), whereas success rate of 88–95% was observed when utilizing intranasal dexmedetomidine–midazolam combination ( 12 , 22 ). Nevertheless, low pH and undiluted midazolam is associated with unpleasant burning sensation and may eaisly disrupt nasal mucosa and nerves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It allays preoperative anxiety in children and improves their cooperation during procedures [33]. A study by Cossovel et al suggested that the combination of intranasal dexmedetomidine in the dose of 2μg/kg and oral ketamine in the dose of 3mg/kg can help in satisfactory separation of the child from the caretaker, allow better success rates of venous cannulation, and smooth induction of general anesthesia [34]. According to Darlong et al, the combination of 3 mg/kg oral ketamine and 0.25 mg/kg midazolam has minimal side effects and allows rapid induction of anesthesia when compared to using either of the drugs alone [35].…”
Section: Anesthetic Usesmentioning
confidence: 99%
“…It is also the agent of choice for induction in children with reactive airway disease and difficult airways because of its broncho-dilating effect [6]. When ketamine is used as a co-induction agent with propofol, midazolam, or dexmedetomidine, it provides the benefits of hemodynamic stability, reduced pain on injection, and less respiration depression [34,35].…”
Section: Anesthetic Usesmentioning
confidence: 99%